Fabrication of flexible light shutter using liquid crystals with polymer structure. Issue 9 (15th July 2017) - Ji, Seong-Min; Huh, Jae-Won; Kim, Jin-Hun; Choi, Yeongyu; Yu, Byeong-Hun; Yoon, Tae-Hoon
ABSTRACT: We fabricated a light shutter using plastic substrates for high visibility of a flexible see-through display. To achieve a flexible light shutter using liquid crystals (LC), it is essential to maintain the cell gap when the light shutter is bent. We studied methods to fabricate flexible LC light shutters using plastic substrates. We demonstrated light shutters that are initially transparent and flexible with or without polymer walls. We have elucidated that polymer walls and networks provide mechanical stability against the bending of an LC light shutter without any degradation in the electro-optic characteristics. We predict that a flexible light shutter provides not only high visibility but also mechanical stability to a flexible see-through display by positioning it at the back of a flexible see-through display panel. Graphical Abstract: